Infective endocarditis (IE) first diagnosed at autopsy: analysis of 31 cases in Ribeirão Preto, Brazil - FIGUEIREDO, Luiz Tadeu M.; RUIZ-JUNIOR, Everaldo; SCHIRMBECK, Tarciso (Revista do Instituto de Medicina Tropical de São Paulo, 2001)
Thirty one infective endocarditis (IE) fatal cases whose diagnosis was first obtained at autopsy were studied. The clinical data of these patients (Group 1) showed significant differences compared to other 141 IE cases (Group 2). The average age of 53 years in Group 1 patients was 18 years higher than that of Group 2. The Group 1 patients had a low frequency of IE predisposing heart disease. Both patient groups presented fever (about 87%), but a significant low frequency of cardiac murmur (25.8%) was observed in Group 1 patients and echocardiography tests were performed in only 16.1%, suggesting that IE diagnosis was not suspected. Likewise, although most Group 1 patients appeared with severe acute illness, they did not present the classic IE clinical presentation. Blood cultures were performed in only 64.5% of the Group 1 patients. However, bacteria were isolated in 70% of these blood cultures and Staphylococcus aureus was isolated in 71.4%. The bacteria attacked mitral and aortic valves. Complications such as embolizations and cardiac failure occurred in almost half of the cases and they also presented with infections of the lungs, urinary tract, and central nervous system. Medical procedures were performed in practically all fatal cases whose diagnosis was first obtained at autopsy. Sepsis occurred in about half of the patients and it was followed by shock in more than 25%. This form of IE must be suspected in mature and in old febrile hospitalized patients having infection predisposing diseases, embolization, and suffering medical procedures.